2022
DOI: 10.3390/nu14040867
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles and Key Mechanisms of Hawthorn Extract against Various Liver Diseases

Abstract: The genus Crataegus (hawthorn), a flowering shrub or tree, is a member of the Rosaceae family and consists of approximately 280 species that have been primarily cultivated in East Asia, North America, and Europe. Consumption of hawthorn preparations has been chiefly associated with pharmacological benefits for cardiovascular diseases, including congestive heart failure and angina pectoris. Treatment with hawthorn extracts can be related to improvements in the complex pathogenesis of various hepatic and cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Diosgenin is abundant in yam, Study confirmed that the abundant diosgenin in yam could suppress excessive weight gain, reduce serum levels of total cholesterol and triglycerides, and decrease liver fat accumulation in high-fat diet-induced NAFLD rats ( Zhou Y et al, 2022 ). Hawthorn could reduce blood lipid, especially serum TG level ( Al Humayed, 2016 ; Han et al, 2016 ; Kim et al, 2022 ). Curcumin in turmeric could reduce blood lipid ( Jarhahzadeh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin is abundant in yam, Study confirmed that the abundant diosgenin in yam could suppress excessive weight gain, reduce serum levels of total cholesterol and triglycerides, and decrease liver fat accumulation in high-fat diet-induced NAFLD rats ( Zhou Y et al, 2022 ). Hawthorn could reduce blood lipid, especially serum TG level ( Al Humayed, 2016 ; Han et al, 2016 ; Kim et al, 2022 ). Curcumin in turmeric could reduce blood lipid ( Jarhahzadeh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the AMPK signaling pathway has been shown to be associated with the alleviation of metabolic disorders in many studies on the treatment of NAFLD. Activation of AMPK signaling pathway is a common feature of NAFLD treatment ( Chen et al, 2019 ; Zhou et al, 2021 ; Chen et al, 2022 ; Kim et al, 2022 ; Liao et al, 2022 ; Zhang and Feng, 2022 ). Activated AMPK signaling pathway in the liver reduces NAFLD mainly by reducing lipid production in the liver and regulating fatty acid oxidation in the liver ( Day et al, 2017 ; von Loeffelholz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ; Kim et al. 2022 ;). As a medicinal and edible plant, there are few reports on the research of C. scabrifolia at present, which only reported its chemical constituents (Dahmer and Scott 2010 ).…”
Section: Introductionmentioning
confidence: 99%